Case Report: Molecular autopsy underlie COVID-19-associated sudden, unexplained child mortality - Unuma, Kana; Tomomasa, Dan; Noma, Kosuke; Yamamoto, Kouhei; Matsuyama, Taka-aki; Makino, Yohsuke; Hijikata, Atsushi; Wen, Shuheng; Ogata, Tsutomu; Okamoto, Nobuhiko; Okada, Satoshi; Ohashi, Kenichi; et al. (Frontiers in Immunology, 2023)
Herein, we report a child with COVID-19 and seemingly no underlying disease, who died suddenly. The autopsy revealed severe anemia and thrombocytopenia, splenomegaly, hypercytokinemia, and a rare ectopic congenital coronary origin. Immunohistochemical analysis demonstrated that the patient had acute lymphoblastic leukemia of the B-cell precursor phenotype (BCP-ALL). The complex cardiac and hematological abnormalities suggested the presence of an underlying disease; therefore, we performed whole-exome sequencing (WES). WES revealed a leucine-zipper-like transcription regulator 1 (LZTR1) variant, indicating Noonan syndrome (NS). Therefore, we concluded that the patient had underlying NS along with coronary artery malformation and that COVID-19 infection may have triggered the sudden cardiac death due to increased cardiac load caused by high fever and dehydration. In addition, multiple organ failure due to hypercytokinemia probably contributed to the patient's death. This case would be of interest to pathologists and pediatricians because of the limited number of NS patients with LZTR1 variants; the complex combination of an LZTR1 variant, BCP-ALL, and COVID-19; and a rare pattern of the anomalous origin of the coronary artery. Thus, we highlight the significance of molecular autopsy and the application of WES with conventional diagnostic methods.